Deportation of Foreign Nationals Residing in Indonesian Territory from Human Rights Perspective - Lisa Arianti Kusuma Dewi (Journal of Law and Border Protection, 2019)
A country has the power to refuse entry or deport any foreign citizen who is in the territory of the country. However, the existence of this power does not necessarily make the state arbitrarily treat everyone. There are limits that must be considered, namely the existence of human rights that must be protected and upheld. This paper is written with the intention of examining the implementation of deportation of foreign nationals in Indonesian territory from a human rights perspective. This paper is designed using qualitative data analysis with data collection methods in the form of literature or literature studies.